2022
DOI: 10.1007/s10238-022-00884-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived intrafemoral orthotopic xenografts of peripheral blood or bone marrow from acute myeloid and acute lymphoblastic leukemia patients: clinical characterization, methodology, and validation

Abstract: Acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) are malignant clonal diseases of the hematopoietic system with an unsatisfactory overall prognosis. The main obstacle is the increased resistance of AML and ALL cells to chemotherapy. The development and validation of new therapeutic strategies for acute leukemia require preclinical models that accurately recapitulate the genetic, pathological, and clinical features of acute leukemia. A patient-derived orthotopic xenograft (PDOX) model is est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, Medyouf and colleagues found that the addition of patient-derived mesenchymal stromal cells improved engraftment of CD34 + cells from patients with Myelodysplastic syndromes after intrafemoral injection 16 . Intrafemoral injections are also commonly employed to test leukemic engraftment of Acute Myeloid Leukemia 17 , 18 and Acute Lymphoblastic Leukemia samples 19 , 20 . Finally, intrafemoral injections have been used in a recent clinical trial of hematopoietic stem cell gene therapy of adult and pediatric patients affected by transfusion-dependent ß-thalassemia 21 , demonstrating their clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Medyouf and colleagues found that the addition of patient-derived mesenchymal stromal cells improved engraftment of CD34 + cells from patients with Myelodysplastic syndromes after intrafemoral injection 16 . Intrafemoral injections are also commonly employed to test leukemic engraftment of Acute Myeloid Leukemia 17 , 18 and Acute Lymphoblastic Leukemia samples 19 , 20 . Finally, intrafemoral injections have been used in a recent clinical trial of hematopoietic stem cell gene therapy of adult and pediatric patients affected by transfusion-dependent ß-thalassemia 21 , demonstrating their clinical relevance.…”
Section: Discussionmentioning
confidence: 99%